2000
DOI: 10.1046/j.1439-0280.2000.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of an insecticide application on non‐target arthropods in winter wheat ‐ a field study over 2 seasons

Abstract: The effects of the insecticide lambda‐cyhalothrin (Karate) on non‐target arthropods in winter wheat were studied throughout two successive seasons in 1998 and 1999. The study particularly focussed on the crop in the growing season after insecticide application (also winter wheat) for detection of potential long‐term effects and for determination of the suitability of different sampling methods.The investigations were based on the assumption that arthropod immigration from surrounding areas is limited in large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
(8 reference statements)
0
15
0
1
Order By: Relevance
“…3B). Pyrethroids such as lambdacyhalothrin usually show high toxicity on predatory phytoseiids (Rock, 1979;Croft, 1990;Raudonis, 2006) and spiders (Wick and Freier, 2000;Martins et al, 2009). These facts are of major concern because Arachnidae are the most abundant arthropods in agro-ecosystems (including our study) and predators of a wide range of insect pests (Marc et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…3B). Pyrethroids such as lambdacyhalothrin usually show high toxicity on predatory phytoseiids (Rock, 1979;Croft, 1990;Raudonis, 2006) and spiders (Wick and Freier, 2000;Martins et al, 2009). These facts are of major concern because Arachnidae are the most abundant arthropods in agro-ecosystems (including our study) and predators of a wide range of insect pests (Marc et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
“…arthropods in agro-ecosystems (Costa and Link, 1999;Kharboutli et al, 2000;Colignon et al, 2001;Costa, 2007). Wick and Freier (2000) and Hand et al (2001) showed that lambdacyhalothrin has a high initial impact, but low persistence.…”
Section: Discussionmentioning
confidence: 99%
“…In general, spider populations are significantly lower in areas where pesticides are applied than in untreated areas (Wick & Freier, 2000). It is possible that the effects of pesticides remain the year following application and consequently influence spider populations.…”
Section: Discussionmentioning
confidence: 99%
“…Of major concern are the possible side effects of drift on non-target organisms (both in the crop and on adjacent non-cereal areas) since, with cereals, large areas are treated simultaneously. Broad-spectrum insecticides like λ-cyhalothrin negatively affected several non-target organisms immediately after application [53] . However, such effects were often ephemeral, with rapid recovery and recolonization.…”
Section: Chemical Controlmentioning
confidence: 99%
“…Some European countries place restrictions on using pesticides in and near field margins to protect arthropod communities from spray drift [54] . Inherently more selective compounds like pirimicarb can be used; alternatively, some potent insecticides for cereal aphid control can be applied successfully at considerably reduced dose rates, especially if infestation is late and levels only marginally exceed the action threshold, as shown by [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] for λ-cyhalothrin and pirimicarb. Low dosage strategies are a very important element of IPM in cereals because of the considerably reduced side-effects on predators and parasitoids.…”
Section: Chemical Controlmentioning
confidence: 99%